THE EFFECT OF ENDOTRACHEAL TUBE (ETT) SUCTION MEASURE ON OUR SATURATION LEVELS IN FAILED PETIENTS IN IGD - -, Desmond (JOURNAL HEALTH OF EDUCATION, 2022)
Failure of the airways is a disease found in COPD, where one of the causes ofrespiratory failure is a blockage in the airway including a blockage due to the installation ofEndotracheal Tube (ETT). Treatment performed on patients who experience respiratoryfailure can be successful if at the time of the assessment has obtained data related torespiratory failure, and this will be done well if the understanding of the officer is good. Thepurpose of this study was to analyze whether there is an influence before and after the actionof suctioning the endotracheal tube (ETT) on changes in O2 saturation levels in patients whoexperience respiratory failure. The study was conducted at the Grandmed Lubuk PakamHospital with a sample size of 22, and using the Wilcoxon test, using a quantitative researchdesign with the design was Quasi Experiment with a one-group pretest-posttest, which isbefore taking action to first check the O2 saturation level and after observation of O2saturation levels was performed again. The technique of data collection is done by accidentalsampling technique where only patients who meet with researchers who become researchsamples, use the instrument observation sheet. The results of this study there are significantdifferences where before and after the action of oxygen saturation levels (p<0,000) whichmeans that there is an effect of the action of suctioning mucus before and after the O2saturation level (p<0,05) so Ha is accepted. It is recommended that future researchersinvestigate further different designs and more samples.